Translating science - comparing religions - Hopf, Arian (Contributions to the history of concepts, 2021)
Sir Sayyid Ahmad Khan (1817?1898) was a prominent South Asian reformer of Islam who focused on the reconciliation of science and Islam in his most influential texts. This article aims to analyze the implications of science becoming the dominant discourse in nineteenth-century South Asia for the conception of Islam and religion in general. Sayyid Ahmad is an intriguing example because he actively participated in religious as well as scientific discourses since as early as the 1830s. After a concise outline of his early writings, his stances toward science and reason shall be compared with his later writings, primarily those written after 1870, to uncover the impact of the increasing influence of science in South Asia during the latter half of the nineteenth century. In his later writings, Sayyid Ahmad accomplishes a complex effort of translation, claiming mutual compatibility of science and Islam. The question of how this influences his conception of Islam and religion will be addressed, exploring whether this process should be described as a mere adoption of foreign discourse? Or does it trigger transformative effects?